MODEL PEMBELAJARAN SPEAKING DAN PENCARIAN BAKAT MENYANYI MELALUI INOVASI MENYANYIKAN LAGU DANGDUT BERBAHASA INGGRIS DI SMA ISLAM KELING JEPARA JATENG - Aliyatin, Nafisah (IAIN Ponorogo, 2013)
Abstract: Motivation is a potential and kinetic energy owned by a person that can stimulate and support activities to achieve the goals.Â In order to raise student motivation, teachers require having adequate competence. One of the teachersâ efforts to improve motivation is by doing innovation of Dangdut song in English to develop studentsâ talent and interest. The result of study revealed that innovation of Dangdut song in English had average score= 4.4 at A level with a very high and good categories. Furthermore, Speaking learning model in teaching English at class X had average score= 4.0 at A-level with very high and good categories, and the last was the singing talent search model through Innovation of Dangdut song in English had average scores= 3.7 at the level of the category B with high and good. If the teacher has his own piano and could play it, undoubtedly the process of teaching speaking will be more joyful, challenging, interesting and unique.Â .Ø©ÙØ¬Ø±ÙÙ Ø§ ÙØ§Ø¯ÙÙØ£Ø§ ÙÙØ¥ ÙÙØµÙÙÙ ÙØ§Ù Ø¹Ø£Ø¨ Ù Ø§ÙÙÙÙ ØµØ®Ø´ÙØ§ ÙØ¯Ù Ø©ÙØ±Ù Ø Ø©ÙØ§Ø·Ù Ø©ÙÙ ØªÙ Ø Ø©ÙØ§Ø· Ø²ÙØ§ÙÙØØ§ ÙØ¥ :ØµØ®ÙÙ Â Ø©ÙÙØªØ±Ù Ø³Ø±Ø¯ÙÙ Ø§ Ø§ÙØ¨ Ù Ø§Ù ØªÙÙØ§ ØªÙØ§ÙØ§ÙÙ ØØ§ ÙÙ .ÙÙÙ ÙØªØ¦Ø§ÙÙØ¨ Ø©ÙÙØ¹ØªÙ Ù Ø²ÙØ§ÙÙØØ§ ÙØ°Ù ÙØ±Ø«Ù ÙØ£ Ø³Ø±Ø¯ÙÙ Ø§ Ø¹Ø§Ø·ØªØ³Ø§ ÙÙÙÙÂ ÙØ±ÙØºØªÙØ§Ù Ø¯ÙØ¯Ø¬ØªÙØ§ Ø§Ø°Ù .Ø¨ÙØ§Ø·ÙØ§ ØªØ§Ø¨ØºØ±Ù ØªØ§Ø¡Ø§ÙÙÙØ§ Ø©ÙÙØªØ±ÙÂ Ø©ÙØ²ÙÙÙØ¬ÙØ¥Ø§ Ø©ØºÙÙØ§Ø¨ ØªÙØ¯ÙØ¬Ø§Ø¯ Ø©ÙÙØºØ£ ÙØ±ØºØªØ¨ Ø²ÙØ§ÙÙØØ§ ÙØ°ÙÂ Ù ÙÙØ¹Øª Ø¨ÙÙØ³Ø£Ù .Ø¯ÙØ¬Ù )Ø§Ø¯Ø¬ ÙØ§Ø¹( ÙÙÙØµØªÙØ§ ÙÙ )A( ÙÙØªØ³ÙÙ Ø§ ÙÙ 4Ø4 Ø©ÙØ¯Ø§Ø¹ÙÙ Ø§Ø¨ Ø©Ø¬ÙØªÙÙØ§ ÙÙØ¥ ØªØ¯Ø£ Ø©ÙÙØºÙØ£Ø§ ÙÙÂ ÙÙØªØ³ÙÙ Ø§ ÙÙ 4,0 Ø©ÙØ¯Ø§Ø¹ÙÙ Ø§ ÙÙÙØª )Ø±Ø´Ø§Ø¹ÙØ§ ( ÙØµÙÙØ§ ÙÙ )Ø©ÙØ²ÙÙÙØ¬ÙØ¥Ø§ Ø©ØºÙÙØ§ ( Ù ÙÙØ¹ØªÙØ§Ù Ù ÙØ¹ØªÙØ§ Ø©ÙÙÙ Ø¹ ÙÙ Ù ÙØ§ÙÙØ§ Ø©Ø±Ø§ÙÙ Â Ø¨Ø±Ø¹Â Ù ÙØºØªÙØ§ ÙÙ Ø¨ÙØ§Ø·ÙØ§ ØªØ§Ø¯Ø§Ø¯Ø¹ØªØ³Ø§ ÙØ¹ Ø«ØØ¨ÙØ§ Ø¨ÙÙØ³Ø£ ÙÙ ÙØ±Ø®ÙØ£Ø§Ù .)Ø¯ÙØ¬Ù Ø§Ø¯Ø¬ ÙØ§Ø¹( ÙÙÙØµØªÙØ§ ÙÙ )A(Â Ø§Ø°Ø¥Ù .)Ø¯ÙØ¬Ù ÙØ§Ø¹( ÙÙÙØµØªÙØ§ ÙÙ ) B( ÙÙØªØ³ÙÙ Ø§ ÙÙ 3,7 Ø©ÙØ¯Ø§Ø¹ÙÙ Ø§Ø¨ Ø©ÙØ²ÙÙÙØ¬ÙØ¥Ø§ Ø©ØºÙÙØ§Ø¨ ØªÙØ¯ÙØ¬Ø¯ Ø©ÙÙØºØ£ ÙÙ Ø¯ÙØ¯Ø¬ØªÙØ§Â Ø©ØºÙÙØ§Ø¨ Ù ÙØ§ÙÙØ§ Ø©Ø±Ø§ÙÙ ( Ù ÙÙØ¹ØªÙØ§Ù Ù ÙØ¹ØªÙØ§ Ø©ÙÙÙ Ø¹ ÙÙÙØª ÙÙØ³ Ø²Ø§ÙÙØ¬Ø§ Ø§Ø°ÙØ¨ ÙÙ Ø§Ø¹ØªÙØ§ ÙÙØ¹ Ø§Ø±Ø¯Ø§ÙÙ ÙÙØ§ÙØ¨ ÙÙ Ø³Ø±Ø¯ÙÙ Ø§ ÙØ§ÙÂ .Ù ÙÙØ¹ØªÙØ§Ù Ù ÙØ¹ØªÙØ§ ØªØ§ÙÙÙ Ø¹ ÙÙ ÙØ¨Ø³ Ø§Ø¨Ù ØªØ³ÙÙ Ø§Ø°Ø¥ Ø©Ø²ÙÙ ØªÙ Ù Ø©ÙÙ Ø¯ØØªÙ ÙÂ Ø©ÙÙØ´Â )Ø©ÙØ²ÙÙÙØ¬ÙØ¥Ø§Keywords: Model Pembelajaran, inovasi, bahasa Inggris.